Drain Pain a Bane of Peritoneal Dialysis: Prevalence in a Cohort of Automated Peritoneal Dialysis Patients. - Qayyum, Ahad; Munir, irfan; Anees, Muhammad; Cheema, Shafiq; Mohsin Riaz, Muhammad; Akbar, Hina; Anjum, Roshina; Altaf, Aatiqa (Pakistan Journal of Kidney Diseases, 2025)
Drain pain in peritoneal dialysis is a frequent occurrence that requires readjustment of catheter and some cases transfer to hemodialysis. This study looks at the drain pain among patients on peritoneal dialysis at a tertiary care center. 73 patients on automated peritoneal dialysis were evaluated retrospectively for drain pain. Male 47(64%) were males. Total of 15 (20%) patients had drain pain. The drain pain was both present in continuous ambulatory peritoneal dialysis exchanges and automated peritoneal dialysis sessions. All (100%) patients continued with APD. No patient had to be transferred to hemodialysis because of drain pain. Conclusion: Occurrence of drain pain in our cohort of patients undergoing APD is similar to the reports in the literature.